The oxidative metabolism of sparteine in the Cuna Amerindians of Panama: Absence of evidence for deficient metabolizers - Arias, Tomas D. (1988)
Artículo científico -- Universidad de Costa Rica. Instituto de Investigaciones en Salud, 1988